High-voltage defibrillator unit with increased energy output from a controlled capacitor storage - Gorokhov-Miroshnikov, E. E.; Slyusarev, G. V. (Вестник Северо-Кавказского федерального университета, 2025)
Introduction. It is known that the combination of the main parameters of the defibrillation pulse, such as its duration, leading edge steepness, current amplitude, energy and shape, phase amplitude ratio, should provide a therapeutic effect with minimal damage to the heart. Maintaining the pulse parameters is complicated by the dependence on the discharge circuit resistance determined by the patient's chest resistance. Goal. The study aims to specify the possibility of improving the therapeutic efficacy and safety of defibrillation while reducing the defibrillator’s need for energy to generate a defibrillation pulse. Materials and methods. The methods of compensating for the patient's chest resistance during defibrillation are considered. The effectiveness and safety of defibrillation are largely determined by the defibrillator's ability to regulate the current and energy of the defibrillation pulse. Defibrillators that implement the method of regulating pulse parameters based on energy provide dependence of the pulse duration on the discharge circuit resistance and do not have sufficient therapeutic efficacy for patients with a high chest resistance. Defibrillators using the method of regulating the pulse parameters based on the current are more effective, as they provide optimal durations of the defibrillation pulse with minimum energy within the possible values of the patient's circuit resistance. Results and discussion. It has been experimentally confirmed that the shape of the defibrillation pulse is of fundamental importance for achieving the therapeutic effect. Analysis of the pulse shape of mass-produced defibrillators revealed that they do not use pulses with a flat front, which have additional therapeutic value. It has been established that it is possible to form a pulse with a virtually constant output energy in a wide range of patient resistances. The model of the proposed high-voltage unit shows the possibility of increasing the energy output from the capacitor bank when forming a pulse of optimal duration with a flat front. In this case, parallel-series restructuring of the battery capacitors is used, the algorithm of which is planned depending on the resistance of the patient's chest, which allows increasing the amount of energy given off by more than 85% of the accumulated energy of the capacitor bank. Conclusion. The obtained results can be used to create a new generation of mass-produced defibrillators with better therapeutic capabilities and reduced production costs.